Memristive circuits design under different personality traits based on second-order damping system. (August 2021) - Sun, Junwei; Xiao, Xiao; Liu, Peng; Wang, Yanfeng
Abstract: Up to now, neural networks have been extensively studied, however, few researches have been investigated about neural networks via circuits. In this paper, a memristive circuit under different personality traits based on second-order damping system is designed to realize human gesture, which is composed of perceptron module, emotion generation and evolution module and neural network module. The neural network module includes memristor array module and voltage computing module. The second-order damped system perceptron based on memristor realizes real-time perception and sensory adaptation function to external stimulus. The perceptual intensity generated by the second order damper perceptron based on memristor converges to a certain emotion through memristor emotion circuit, and then expressed by human gesture. Emotional tendency varies from person to person, and the emotional tendency which produced by three kinds of personality is analyzed in this paper. Monte Carlo analysis shows that the perceptron circuit has high robustness, and the mean deviation value is only 0.13 % when the tolerance is 5 % . Furthermore, this circuit can provide a reference for further intelligent machines.